Editors’ Introduction: Fictions in Law, Literature, and Philosophy - Zander, Laura; Celik, Nursan; Luft, Constantin (Law and Literature, 2024)
While several collections have been published recently from the perspective of common law focused specifically on jurisprudence and from the perspective of both literary theory and the philosophy of language, a more integrative approach that sharpens the underlying fundamental concept(s) by bringing together insights from legal theory/history, doctrinal legal scholarship, literary studies, and analytic philosophy has been missing so far. Not only has an examination of a decidedly interdisciplinary perspective been rare in research on fictions and fictionality, but also a decidedly integrative view of European and Anglo-American research approaches has been the exception. This special issue both addresses and seeks to bridge this research gap. In shedding light on the family resemblances and differences of “fiction(s)” in each of the aforementioned disciplines, we hope to identify blind spots and offer some fresh ideas with regard to a transdisciplinary theory of fiction(s) which considers their conceptual, functional, as well as historical characteristics. A particularly significant aspect of this project is that it fuses contributions from an anglophone law and literature perspective with contributions from European continental contexts, offering perspectives from related but also distinct legal and literary traditions.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Fiction; fictionality; Law & Literature; legal fictions; philosophy

The Pretense Mode of Fiction. On the Practice of Fiction in Literary Studies - Celik, Nursan (Law and Literature, 2024)
Since the late twentieth century, fiction, once primarily connected to the arts, has gradually become a much-debated topic in a wide range of research fields and disciplines including law and philosophy. However, as many different disciplines are now increasingly thematizing fiction and various usages of the term “fiction” exist, there is danger of mixing up the different definitions of this term, making it difficult to compare the approaches. In order to enable a comparison between “fiction” in those disciplines which this special issue focusses on, this article discusses fiction from a literary studies perspective. The aim is to unfold what it means for a literary text to be considered fiction and by doing so, elaborate on the peculiarities of fiction in the literary field. To facilitate the comparison, some essential distinctions that have become established in German scholarship require explanation first. The differentiation between fictionality as a potential property of texts and fictivity as a potential property of objects within fiction is rarely found in Anglo-American discussions of fictionality in literature but has become a central distinction in German discussions. By distinguishing between these two levels of fiction, it also becomes clear why reality does not necessarily function as fiction’s opposite—an assumption that can still be found frequently, especially in the everyday usage of the term “fiction.” Furthermore, this article will show that literary fictions do not even have to include invented characters, actions, and events, because the crucial point lies in the specific communicative stance authors of fiction demand from their readers. Hence, simply defining fiction as texts or other media that deal with invented characters, actions, or events would be inaccurate according to recent, pragmatic approaches in literary studies that clearly dominate the contemporary discourse on fiction. From the perspective of pragmatic approaches, what constitutes fiction is a very intricate question and cannot be answered by merely focusing on textual or semantic properties. That fiction cannot be determined through the content level will be demonstrated by evaluating the four most prominent and plausible accounts of fiction. After briefly discussing the pros and cons of these major accounts, I will focus on why this article favors John R. Searle’s approach to fiction, which emphasizes the pretense aspect as the peculiarity of fiction-making in communicative terms. The introduction concludes with a discussion of two core licenses that follow from the pretense strategy for authors of fiction, namely the license to choose any mode of presentation for their fictional story (communicative freedom), and secondly, the license to depict any topic and content they want (ontological freedom). Due to its clarificatory purpose, this essay does not offer a new understanding or even approach to fiction. Instead, it provides an overview of the core ideas regarding literary fiction for a readership that might come from various disciplines, albeit the special focus is on law as this issue’s central one. The article is deliberately written as a concise introduction to major approaches to fiction and fictionality in the field of literary studies or literary theory with a focus on the discussion in German scholarship in comparison to Anglo-American scholarship. This is meant to pave the way for the more detailed interdisciplinary and international discourse and discussion which make up the main bulk of the special issue.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Fiction; fictionality; fictivity; literary studies; pretense; speech acts